Extreme-intensity exercise: exercise tolerance and recovery - Alexander, Andrew Michael (Kansas State University, 2021)
Severe-intensity exercise describes specific exercise intensities where contraction-induced metabolic markers (e.g., inorganic phosphate, H+, pH) do not reach steady-state, but continue to change until task failure is reached. It has been found that the rates of change in these markers are intensity-dependent, but reach similar values at the limit of exercise tolerance (T[subscript lim]). Therefore, the amount of work done at T[subscript lim] is not different across severe-intensity work rates. However, we have previously shown evidence of a supra-severe-intensity domain (i.e., extreme-intensity exercise), where the amount of work performed at T[subscript lim] is significantly lower than during severe-intensity exercise. Further, the mechanisms limiting exercise tolerance reverse at significantly faster rates during recovery from extreme-intensity exercise compared to following severe-intensity exercise. Therefore, the overall aims of this dissertation were to examine the differences in exercise tolerance between severe- and extreme-intensity exercise as well as measure important neuromuscular recovery immediately following exercise cessation in order to elucidate what potential mechanistic differences may be contributing to the accelerated accumulation of fatigue. In our first investigation (Chapter 2), we demonstrated that maximal voluntary contraction (MVC) was significantly decreased following severe- and extreme-intensity exercise. MVC recovery was apparent in both men and women following severe-intensity exercise, with little to no recovery following extreme-intensity exercise. Further, peripheral fatigue, estimated by reductions in potentiated twitch force (Q[subscript pot]), did not develop to the same degree following extreme- compared to severe-intensity exercise and showed significant recovery within 90 s in men and 150 s in women. To further investigate sex differences in neuromuscular fatigue development and force recovery following extreme-intensity exercise, in our second investigation (Chapter 3), we found no differences in W’[subscript sev], or W’[subscript ext], between men and women. MVC and Q[subscript pot] forces recovered faster following extreme-intensity exercise compared to following severe-intensity exercise, with women recovering to values not significantly different from baseline sooner than in men. Further, it was evident that men accumulated greater peripheral fatigue during submaximal exercise than women; however, there were no sex differences following near-maximal (90% MVC) exercise. In our final pilot investigation (Appendix A), we examined the potential effects of creatine monohydrate supplementation on extreme-intensity exercise tolerance. Although no statistical differences were found in MVC, Q[subscript pot], W’[subscript sev], or W’[subscript ext], individuals showed large variability in responses to creatine supplementation, with creatine supplementation having profound effects on exercise tolerance in some, but not all, individuals. Collectively, this dissertation provides novel findings and improves our understanding of exercise intensity domain-dependent fatigue mechanisms and their contributions, especially during extreme-intensity exercise. Further, we provide evidence of differences in neuromuscular recovery between men and women, which are likely to have important implications regarding sex-dependent-mechanisms limiting exercise tolerance. Therefore, it is important to consider the differences between men and women regarding the mechanisms and level of fatigue and time course of recovery when developing exercise prescription (e.g., work rate intensity, recovery between exercise modalities) for specific populations.
Keywords: Severe-intensity exercise; Extreme-intensity exercise; Peripheral fatigue; Central Fatigue; Exercise recovery; Sex differences in response to exercise